DIGITAL CURRENCIES AND INFORMAL ECONOMIES: ASSESSING THE FINANCIAL INCLUSION POTENTIAL OF CBDCs IN EMERGING MARKETS - Loso Judijanto; Ajeng Faizah Nijma Ilma; Farikhul Muafiq (Adisam Publisher, 2025)
This research aims to explore the potential of central bank digital currencies (CBDCs) to increase financial inclusion in emerging markets, particularly in the context of the informal economy, which still dominates economic activity in many regions. Through a comprehensive literature review of previous studies, policy reports, and international regulatory documents, this research analyzes how the design and implementation of CBDCs can bridge the financial access gap faced by marginalized groups and workers in the informal sector. The study finds that CBDCs have significant potential to provide cheaper, safer, and more accessible payment systems, as well as increase trust in the formal financial system. However, these benefits are highly dependent on factors such as technical design, public trust, digital infrastructure, and privacy protection policies. This research recommends that the development of CBDCs in developing countries seriously consider the local socio-economic context and foster close collaboration between governments, the private sector, and local communities to ensure inclusive and sustainable adoption.